2020
DOI: 10.1371/journal.pone.0239803
|View full text |Cite|
|
Sign up to set email alerts
|

Mediterranean diet and quality of life in women treated for breast cancer: A baseline analysis of DEDiCa multicentre trial

Abstract: Evidence suggests a beneficial role of the Mediterranean Diet (MedDiet) on health-related quality of life (HRQoL) in healthy subjects. HRQoL is relevant in cancer therapy and disease outcomes, therefore we investigated the association between adherence to the MedDiet and HRQoL in breast cancer survivors participating in the multicentre trial DEDiCa. Diet and HRQoL were assessed at baseline in a subgroup of 309 women enrolled within 12 months of breast cancer diagnosis without metastasis (stages I-III, mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…We had previously demonstrated that higher adherence to the Mediterranean diet in BC survivors was associated with higher HRQoL, particularly for physical functioning, sleep, pain and overall well-being [4]. Generally, a healthy dietary pattern is associated with better HRQoL [17,18,33,34] including fatigue which is prevalent in BC survivors and is associated with shorter overall survival [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We had previously demonstrated that higher adherence to the Mediterranean diet in BC survivors was associated with higher HRQoL, particularly for physical functioning, sleep, pain and overall well-being [4]. Generally, a healthy dietary pattern is associated with better HRQoL [17,18,33,34] including fatigue which is prevalent in BC survivors and is associated with shorter overall survival [35].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in BC incidence and the high survival rates among BC patients indicate the importance of targeting health-related quality of life (HRQoL) and understanding its relationship with lifestyle including diet and physical activity. Healthy lifestyles have been associated with better quality of life [4] which is in turn associated with favorable prognosis and lower mortality [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding, a few interesting papers could indicate the positive effects of the MD on the progression of breast carcinoma. For example, it has been reported that the MD may contribute to reducing breast cancer recurrence in patients with invasive breast cancer [ 116 ], and that adherence to the MD in breast cancer survivors is associated with a better quality of life [ 117 ]. Lastly, a pilot study has reported that the supplementation of vitamin D in women with metastatic breast cancer and insufficient 25-hydroxyvitamin D (25[OH]D) serum levels improves bone pain and fatigue [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mostly, the data is used for assessing interventions, quality indicators and for following up the quality of care [30]. The EQ-5D-3L has also been used in previous studies on cancer survivors and late toxicity effects after cancer treatment [31][32][33][34]. In the study by Yu et al on breast cancer survivors in Korea, there was no difference in the EQ-5D-3L index in general between survivors and an agematched control group 5 years after surgery; however, in the categories of pain/discomfort and anxiety/depression, the survivors still scored worse than the controls [34].…”
Section: Introductionmentioning
confidence: 99%